MOTORCYCLE ACCIDENTS: CHARACTERISTICS AND SUSPECTED ALCOHOL USE - Bárbara de Jesus Cunha da Silva; José Diego Marques Santos; Ana Maria Ribeiro dos Santos; Maria Zélia de Araújo Madeira; Marcia Teles de Oliveira Gouveia (Universidade Federal do Paraná, 2017)
The present study aimed to analyze the relationship between the characteristics of motorcycle accidents and suspected alcohol use. Descriptive and cross-sectional study with 110 patients involved in motorcycle accidents assisted at an emergency hospital in a large city (state capital) in Northeastern Brazil. Data was collected in November-December 2016 and analyzed through descriptive statistics and inferential tests. Significant associations were found between alcohol consumption and injury severity, licensed or unlicensed drivers, time of the accident (night or day) and helmet use. Most victims of motorcycle accidents were not using a helmet and had consumed alcoholic beverages. The findings call attention to the need for a direct, effective and sustainable traffic crash surveillance system by the responsible bodies, given the lack of effective preventive measures.